Determinants of risk premiums on forward contracts for Kansas wheat - Waldie, Kyle (Kansas State University, 2014)
Forward contracts are one of the main tools used by producers to manage price risk because forward contracts shift the risk from producers to the grain elevator offering the contract. The elevators protect themselves from this risk by hedging, leaving them susceptible to basis risk, which they offset by adding a risk premium to the forward contracts they offer producers. This risk premium is affected by increased volatility and by differences in elevator-specific characteristics at elevator locations across Kansas. This study replicates the results in Taylor, Tonsor, and Dhuyvetter (2013) and adds a set of elevator-specific characteristics to measure their effect on risk premiums. A random effects generalized least squares model is estimated due to the data gathered being panel data. The contribution of this study is to further examine the drivers of risk premiums in forward contracts for Kansas wheat. The results indicate that all of the elevator-specific characteristics in the data set have a statistically significant impact on the value of risk premiums on forward contracts for Kansas wheat. The results also confirm the findings in Mallory, Etienne, and Irwin (2012) and Taylor, Tonsor, and Dhuyvetter (2013) that increased volatility post 2007 caused increases in risk premiums. The risk premiums after the structural break in 2007 increased by $0.069695/bushel, as the average risk premium prior to 2008 was $0.158682/bushel, while the average risk premium after 2007 was $0.228378/bushel.
Keywords: Forward contracts; Risk premiums; Kansas wheat; Elevator characteristics; Economics, Agricultural (0503)